CONSUMERS PURSUING A SENSE OF SOCIAL PRESENCE: EMOTIONAL ENGAGEMENT OR FUNCTIONAL ENGAGEMENT - Praphruetmon, Chenicha (วารสารปัญญาภิวัฒน์, 2022)
Consumers are sometimes willing to pay higher prices for specific products or services (such as global brands). In the media field, academics and practitioners have long been concerned and explored the possible reasons. Using a sample of 356 Thai consumers, through SEM and regression analysis hypothesis testing, it was found that, based on media richness theory, this study aims to investigate the effect of media richness on two types of engagement (affective engagement and functional engagement) affected by social presence. Impact on consumer attitudes of global brands. Influencing consumer attitudes toward global brands. Combining the relevant literature to build a theoretical model will help people understand how those higher production values are formed in the minds of consumers. The model can provide further exploration for scholars interested in this topic and can also help companies apply in marketing communication, market segmentation, target market selection, and product positioning.